EFFECT OF SALINITY STRESS ON GERMINATION OF FIVE TUNISIAN LENTIL (LENS CULINARIS L.) GENOTYPES - Ouji, Ali; El-Bok, Safia; Mouelhi, Mohieddine; Younes, Mongi Ben; Kharrat, Mohamed (European Scientific Journal, ESJ, 2015)
Salinity is one of the major stresses especially in arid and semi-arid regions, which severely limites crop production. It is a significant problem affecting agriculture worldwide and is predicted to become a larger problem in the coming decades. This study was conducted to assess the effect of different salinity level (0, 50, 150, 250 mMol of NaCl) on lentil seed germination efficiency (germination, seedling shoot length, seedling root length, seedling fresh shoot weight and seedling fresh root weight). Five Tunisian genotypes of lentil (Lens culinaris M) namely: Kef, Siliana, Nefza, Ncir, and Local oueslatia were investigated. Results showed that there were significant differences among the different NaCl solution for all evaluated traits. Indeed, the experiment showed that the concentrations of salt have a negative impact on the germination and growth of lentil. As a result when the concentration of salt increases, the germination, length of root and shoot and fresh weight of root and shoot decreases. At 250 mM salt stress level, seed germination percentage of all genotypes was notably reduced compared with non-stress condition (0.0 mMol). Moreover, the seeds were not germinated by the 250 mM salinity level for kef genotype. From the results of this present investigation, it can be concluded that seeds of Kef and Ncir genotypes were susceptible to higher concentrations of salt solutions in germination stage. However, Siliana, Local oueslatia and Nefza genotypes can be considered as tolerant to salt stress compared to the other ones. These genotypes could be used for further analysis and for hybridization in the breeding program for enhancing lentil cultivation in newly reclaimed soils.